Motivasi Petani dalam Optomalisasi Pemanfaatan Pekarangan di Kecamatan Puncak Sorik Marapi - Ameilia Zuliyanti Siregar; Nurliana Harahap; Layla Rahma Hayati (AGRITEXTS: Journal of Agricultural Extension, 2021)
Fulfillment of food at the individual level is carried out through activities to optimize the use yards, this activity is intended to anticipate food insecurity in various regions. Utilization of yards is managed through approach of integrated agriculture of types plant, livestock and fish farming, to ensure the continuous availability of diverse foods, in order to fulfill family nutrition. The research objectives are to verify the level of farmers motivation which optimizing the utilization of their yards in Puncak Sorik Marapi District. The research uses descriptive analysis by a quantitative approach. Furthermore, the data were collected by a questionnaire instrument which it had tested for validity and reliability, using multiple linear regression and a Likert scale. The study resulted show that level farmers motivation which optimizing the use of yards in Puncak Sorik Marapi District is in the very high category, namely 80.81%, while the results of linear regression onwhich farmer motivation influenced by optimizing used yards are obtained by the following equation Y = - 0.980 + 0.136x_1-0.023x_2 + 0.432x_3 + 0.135x_4. Further tests using t-count showed that the factors that the significant effect on motivation farmers in optimizing use of their yards were farmers' perceptions (2.651), the role of extension workers (5,464), and farmer characteristics (2.894).